Evaluation of a pressure pulse in a fractured‐rock aquifer to reduce uncertainty of hydraulic conductivity measurements, Rio Grande Rift, New Mexico, United States. (27th March 2013) - Langman, Jeff B.; Engdahl, Nicholas B.
Abstract Fractured‐rock aquifers are inherently difficult for determining flow dynamics because of variability in fracture orientation and extension. A confined, fractured‐rock aquifer in a semi‐arid mountainous area of the Rio Grande Rift Zone was analysed for its response to recharge events that produced a pressure pulse within its potentiometric surface. The pulse was evaluated at the well scale and subaquifer level to evaluate flowpaths, travel times and dispersion and compare the bulk‐scale aquifer response to possible velocities from slug test hydraulic conductivity measurements. Travel time and dispersion from the pulse proved comparable to probable travel times based on hydraulic conductivity measurements. Evaluation of the pressure pulse and the hydraulic conductivity measurements allowed for a holistic interpretation of the fractured‐rock aquifer through analysis of two distinct data sets that provided corroborative evidence of flow dynamics and fracture connectivity. This holistic approach reduced uncertainty regarding the individual hydraulic conductivity values.